THE EFFECTIVNESS OF USING MEMRISE APPLICATION TOWARD VOCABULARIES MASTERY STUDENTS OF FOUR GRADE AT ALAM ELEMENTARY SCHOOL - dwi warni, desi (Journal Of Language Education and Development (JLed), 2022)
ABSTRACT The problem in this reseach is were related to vocabulary pronunciation and memory which were still lacking and maybe this application could help students remember and repeat the vocabulary he already knows so that it is not easily forgotten When the learning process takes place,one that will hinder learning new vocabulary because it might be the medium used boring or monotonous. In the learning process consider teaching vocabulary, there will be new and different things that make students interestedhelp them learn new vocabulary, not only memorized, but also applicable. This reseach is quantiatitative ,this reseach was use experimental reseach method with experimental design , the subjects of four grade are 20 students , The data collection technique is pre-test, post-test, and treatment ,the reseach was use vocabulary test is 10 multiple choice . The results of reseach data analysis show that use of , there was effectiveness of using memrise application towards students' vocabulary mastery at alam elementary school for fourth grade .this can be seen from the pre-test the score of pretest is 49,9 before given treatment of memrise application , and the score of post –test is 74,7 after given treatment of memrise application ,it can be effectiveness that use of memrise application . Keyword : Vocabulary Mastery, Memrise Application